Conflict between Women's Physically Active and Passive Leisure Pursuits: The Role of Self‐Determination and Influences on Well‐Being. Issue 2 (13th February 2014) - Williams, Tamara; Guerin, Eva; Fortier, Michelle
<x xml:space="preserve">Abstract</x> Background: Evidence in support of both physically active and passive leisure as significant contributors to well‐being has surfaced around the world. However, for physically active, working mothers, fitting leisure into an already busy schedule can be challenging. The purpose of this study was to examine the influence of time resources and self‐determination for active and passive leisure on conflict between these two leisure domains and the influence of this conflict on well‐being. Methods: A total of 66 working mothers completed validated questionnaires measuring satisfaction with time and motivation at baseline followed by two weeks of computerized diary capture to evaluate leisure engagement with final measures of goal conflict and well‐being at the end of the two weeks. Results: Results indicated that dissatisfaction with time resources is associated with increased goal conflict as are non‐self‐determined motivation for physically active leisure and self‐determined motivation for passive leisure. Controlling for engagement in physically active and passive leisure, well‐being is negatively influenced by goal conflict. Conclusions: Time resources, goal conflict, and motivation are important factors to consider in efforts to increase well‐being among physically active working mothers. Further research is required to understand the influence of opposing motivational orientations on goal conflict.